Recognition of Ionic Liquids as High-Voltage Electrolytes for Supercapacitors - Pan, Shanshan; Yao, Meng; Zhang, Jiahe; Li, Bosen; Xing, Chunxian; Song, Xianli; Su, Peipei; Zhang, Haitao (Frontiers in Chemistry, 2020)
The electrochemical stability of electrolytes is essential to the working potential of supercapacitors. Ionic liquids (ILs) are being considered as safe alternatives to current organic electrolytes and attracting extensive interests owing to their inflammability, widened potential windows, and superior ionic conductivity. Novel supercapacitors with ILs electrolytes exhibit attractive energy density and can be utilized in various energy storage systems. Most previous studies focused on electrochemical performances while rare attentions were devoted to energy storage process details or mechanisms. This review comprehensively summarizes the latest progress on formulated ILs electrolytes for different types of supercapacitors, with an emphasis on the intrinsic understanding of the related energy storage mechanisms. Subsequently, comparison of various ILs based liquid-state electrolytes, as well as the state-of-the-art advancements in optimizing ILs electrolytes are introduced. The authors attempt to reveal the inherent correlation between the usage of ILs electrolytes and the properties of supercapacitors via referenced works. Some emerging applications of ionogel electrolytes based on conventional polymers and poly(IL)s for flexible supercapacitors are also presented, including the existing problems. In addition, challenges and future perspectives of research in this field are highlighted.